Resiliensi Perempuan Saat Pandemi Covid-19 Di Objek Wisata Curug Jenggala, Baturraden, Banyumas (Laboratorium Sosiologi FISIP Universitas Jember, 2023)
Economically, women are the figures most affected by the recent Covid-19 pandemic. Women must try hard to protect their family members from Covid-19. At the same time, women also have to meet the economic needs of the family which is disrupted by restrictions on community economic activities. This research is aimed at uncovering the resilience conducted by women, especially those who work in the tourism sector in dealing with the Covid-19 pandemic. This research was conducted by qualitative methods in Kalipagu, Ketenger Village, Baturraden, Banyumas Regency. Data collection was carried out through in-depth interviews to women who work in the tourism sector whom selected purposively as the subject of this study. The results of the research show that in facing the Covid-19 pandemic disaster, women have taken several ways to survive, including by saving money and prioritizing spending, utilizing garden produce for sale as well as for food needs; doing side jobs; using savings; and borrowing money or debt is the last alternative to survive. Keywords: women, resilience, tourism, pandemic